2015
DOI: 10.1111/hpb.12515
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasonography as a direct measure of evolving respiratory dysfunction and disease severity in patients with acute pancreatitis

Abstract: Background: The value of lung ultrasonography in the diagnosis of respiratory dysfunction and severity stratification in patients with acute pancreatitis (AP) was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…1922 In pneumonia-caused ARDS, increasing age and comorbidities were associated with high risk of developing ARDS. Surprisingly, there were no statistically significant differences in age and comorbidities among SAP patients with or without ARDS in the present study, which was consistent with previous studies among patients with SAP 23,24 and AP, 16,25 indicating that age and comorbidities is not as much of a risk factor in SAP-related ARDS as in pneumonia-initiated ARDS. Although hypertriglyceridemia-induced AP has been reported to be associated with risk of lung failure compared with other etiologies, 16,26 the etiologies of SAP have no significant differences between the groups with or without ARDS.…”
Section: Discussionsupporting
confidence: 92%
“…1922 In pneumonia-caused ARDS, increasing age and comorbidities were associated with high risk of developing ARDS. Surprisingly, there were no statistically significant differences in age and comorbidities among SAP patients with or without ARDS in the present study, which was consistent with previous studies among patients with SAP 23,24 and AP, 16,25 indicating that age and comorbidities is not as much of a risk factor in SAP-related ARDS as in pneumonia-initiated ARDS. Although hypertriglyceridemia-induced AP has been reported to be associated with risk of lung failure compared with other etiologies, 16,26 the etiologies of SAP have no significant differences between the groups with or without ARDS.…”
Section: Discussionsupporting
confidence: 92%
“…Macrophages promote cell apoptosis through phagocytic cell debris and secretion of cytokines, thereby aggravating the inflammatory response. [15] Our study found that in children with primary short-term relapse of intussusception, the expression of MCP-1 in the peripheral blood was significantly greater than that of non-relapsed children. Some scholars have pointed out that the occurrence of primary intussusception has a clear relationship with some inflammatory mediators, such as IL-6.…”
Section: Discussionmentioning
confidence: 68%
“…Clinical evidence of respiratory failure may not be obvious in these patients, and only 11% of these patients have radiological evidence of respiratory complications . The radiological changes are in the form of patchy infiltrates on chest radiography and as patchy areas of consolidations and atelectasis on CT …”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…A greater number of comet tail artifacts are described in patients with respiratory dysfunction, severe disease, and with elevated C‐reactive protein (CRP). It was found to be particularly useful when only ultrasound of the nondependent lung (lower lateral and upper quadrants) was performed …”
Section: Pulmonary Complicationsmentioning
confidence: 99%